Evaluation of crude microcrystalline cellulose from theobroma cacao L. (fam. Malvaceae) (Cacao) pod husks as suspending agent in oral suspensions - Palomares, Shania Jyra Q.; Ladignon, Ethel Andrea C.; Tsai, Kristi Yana Fae N.; Vergara, Angela May R. (Manila Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2025)
Theobroma cacao L. is an evergreen fruit tree primarily cultivated for its beans, which are typically used in the food, cosmetic, and pharmaceutical industries. However, since the beans only comprise 27-29% of the fruit, the remaining 70%, the cacao pod husk (CPH), is often discarded as waste. CPH is rich in cellulose, making it a viable source of pharmaceutical excipients; microcrystalline cellulose included. This study aimed to formulate an oral suspension using microcrystalline cellulose (MCC) extracted from the cacao pod husks (CPH) as a suspending agent. The CPH-MCC was extracted by performing base hydrolysis, bleaching, and acid hydrolysis consecutively. The extracted CPH-MCC was then characterized using selected physicochemical and pharmacopeial tests (organoleptic evaluation, identification test, pH, loss on drying, swelling capacity, and FTIR), before being utilized in the formulation of paracetamol oral suspensions to determine its suspending ability. Evaluation of the oral suspension was performed based on its physical properties, specifically: organoleptic evaluation, pH, redispersibility, sedimentation volume, and viscosity.

MCC was extracted from CPH with a total yield of 3.89% from 1275 g of dried CPH. CPH-MCC passed the organoleptic evaluation, identification test Method B in USP (violet-blue), pH (6.3), and loss on drying (5.3% ± 0.17). Swelling capacity of CPH-MCC (72.22% ± 4.81) was higher than the standard MCC. FTIR analysis showed the functional groups present in the sample, which were consistent with the IR spectra of MCC from various references. The formulated oral suspension was not able to meet the acceptance criteria for the following quality tests: organoleptic evaluation, redispersibility, and sedimentation volume, which is attributable to the low viscosity of the suspension. Recommendations include the full characterization of the extracted CPH-MCC, optimization of the bleaching process in the extraction, and further exploration of possible pre-treatment of the MCC/CMC mixture.
Thesis (Bachelor of Science in Pharmaceutical Sciences)--University of the Philippines Manila, June 2025
Keywords: Suspending agents (Pharmacy) -- Natural products -- Agricultural by-products.; Microcrystalline cellulose -- Evaluation -- Pharmaceutical excipients -- Philippines; Theobroma cacao -- Pod husks -- Utilization -- Plant fibers -- Drug formulation; Cacao pod husk; Microcrystalline cellulose; Suspending agent